Antioxidant enzyme activity in heat-treated strawberries (Fragaria vesca L.) combined with salicylic acid - Coltro Roncato, Sidiane; Broti Rissato, Bruna; Meinerz, Cristiane Claudia; Della Valentina Gonçalves, Edilaine; Forlin Dildey, Omari Dangelo; Broetto, Laline; Barrientos Webler, Tulya Fernanda (Revista Colombiana de Investigaciones Agroindustriales, 2017)
Postharvest strawberry treatments are needed to induce resistance and increase the shelf life without loss of quality. Therefore, this study aimed to evaluate the effect of postharvest heat treatment in combination with salicylic acid in the antioxidant activity, enzymatic and incidence of fungi in the strawberry during storage. The experimental design was completely randomized in a 4x4 factorial design with four replications. Strawberries grow Dover were subjected to the following treatments: heat treatment (45 ° C for 3 h in an oven), application of salicylic acid (immersion for five minutes in 2.0 mM aqueous solution), combination of heat treatment with salicylic acid and control (untreated). Were stored for 1, 7, 14 and 21 days under refrigeration at 5 ° C with 90-95% relative humidity. The enzymatic activity of peroxidase (POD) occurred in the initial period of 1 to 7 days of storage strawberries treatment heat and with salicylic acid. Regarding the combination of salicylic acid and heat treatment occurred enzymatic activity in the presence of fungi. For polyphenol oxidase (PPO) activity, heat treatment showed an oscillation of activity, while salicylic acid and the combination of and salicylic acid with treatment heat showed no significant differences, and showed constant activity of PFO. For the treatment with salicylic acid the strawberries showed only 5% fungal incidence. The antioxidant activity of strawberries treated with salicylic acid was high in all periods except at 21 days.